2022
DOI: 10.48550/arxiv.2201.08208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the existence of flips for threefolds in mixed characteristic $(0,5)$

Abstract: We provide a detailed proof of the validity of the Minimal Model Program for threefolds over excellent Dedekind separated schemes whose residue fields do not have characteristic 2 or 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…When the pair is pseudo-effective more is known, it is shown that in fact every MMP terminates without the need for scaling [2,Theorem 9.8]. Subsequent work in [12] establishes analogous results in the đť‘ť = 5 case. For the special case of semi-stable fibrations, [11] covers the case of semi-stable threefolds without constraint on the characteristic, while [4] and [13] show MMP's exist over Dedekind domains with perfect residue fields of characteristic đť‘ť > 5.…”
Section: Introductionmentioning
confidence: 89%
“…When the pair is pseudo-effective more is known, it is shown that in fact every MMP terminates without the need for scaling [2,Theorem 9.8]. Subsequent work in [12] establishes analogous results in the đť‘ť = 5 case. For the special case of semi-stable fibrations, [11] covers the case of semi-stable threefolds without constraint on the characteristic, while [4] and [13] show MMP's exist over Dedekind domains with perfect residue fields of characteristic đť‘ť > 5.…”
Section: Introductionmentioning
confidence: 89%